Interactions between intraseasonal and diurnal variability of precipitation in the South Central Pacific: The case of a small high island, Tahiti, French Polynesia. (14th September 2018) - Hopuare, Marania; Guglielmino, Mathieu; Ortega, Pascal
Abstract : Intraseasonal and diurnal variability of precipitation over Tahiti, French Polynesia, are investigated with the use of wind regimes as intermediary tools. Four wind regimes have been determined over a large domain around Tahiti in the wet season. It has been shown that some phases of the Madden–Julian Oscillation (MJO) trigger some regimes and undermine some others. The diurnal cycle of precipitation in Tahiti is composed of two rainfall maxima. A frequent maximum at midnight but with a low value. An afternoon maximum, less frequent but with a higher value. We have noticed that the afternoon rainfall maximum, which is a reasonable consequence of the sea breeze circulation, is smoothen on the windward side when vigorous wind regimes obstruct the development of the sea breeze. We have also found that daily mean precipitation is significantly increased during MJO Phases 7 and 8, and reduced during Phases 2 and 3. Phase 8 is the wettest phase on Tahiti, suggesting the convective envelope is overlooking the island. Lastly, we have provided evidence that the diurnal cycle of rainfall is significantly affected by the MJO. Indeed, both the midnight and afternoon maxima increase during MJO Phase 7. The most quiescent wind regimes are triggered during Phase 7, as a result from the propagation of the westerly wind anomaly, which allow the development of the sea breeze circulation and the increase of the afternoon peak. For MJO Phase 8, however, the above relationships break down, as the diurnal cycle is not enhanced by the predominant quiescent wind regimes. We assume that the MJO convective envelope covers the island and stays several days, preventing the solar heating of the surface, hence the development of the land/sea breeze circulation, and foremost leads to higher amounts of rainfall as the Phase 8 is the wettest phase on Tahiti. Abstract : Diurnal cycle of rainfall averaged over the spatial clusters for each wind regime.